Sin - Quell, Gottfried, 1896-; Bertram, George; Stahlin, Gustav; Grundmann, Walter, 1906-1976; Coates, John Rider, 1879- (London, UK Adam and Charles Black, 1951)
Includes bibliographical references.
Keywords: Sin -- biblical teaching